2020
DOI: 10.3390/jsan10010003
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Techniques for Implementing Elliptic Curve Point Multiplication on Hardware

Abstract: Cryptography is considered indispensable among security measures applied to data concerning insecure means of transmission. Among various existent algorithms on asymmetric cryptography, we may cite Elliptic Curve Cryptography (ECC), which has been widely used due to its security level and reduced key sizes. When compared to Rivest, Shamir and Adleman (RSA), for example, ECC can maintain security levels with a shorter key. Elliptic Curve Point Multiplication (ECPM) is the main function in ECC, and is the compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The algorithm also will allow the implementation of ubiquitous intelligent services for vehicular users [62]. Finally, future work will integrate the algorithm with strategies used to treat Context Histories [63][64][65][66] such as pattern analysis [67], context prediction [68], similarity analysis [69], cryptography [70], and IoT challenges in smart environments [71,72]. This integration will support better solutions; specifically, to routing problems and in general for problems involving context histories.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm also will allow the implementation of ubiquitous intelligent services for vehicular users [62]. Finally, future work will integrate the algorithm with strategies used to treat Context Histories [63][64][65][66] such as pattern analysis [67], context prediction [68], similarity analysis [69], cryptography [70], and IoT challenges in smart environments [71,72]. This integration will support better solutions; specifically, to routing problems and in general for problems involving context histories.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarizes the use intensity of each coordinate system by the different research works published in the literature. From this table, we can find that the majority of the studied works have shown that the Lopez and Dahab coordinates implemented in binary fields are the least expensive in terms of the number of operations required for the scalar multiplication calculation [ 87 ]. For this reason, the Lopez and Dahab coordinates present the best choice to be adopted in order to achieve a scalar multiplication implementation suitable for constrained applications.…”
Section: Elliptic Curve Cryptographymentioning
confidence: 99%
“…Security is becoming one of the top concerns in Cyber-Physical Systems and Internet-of-Things (IoT) devices [1]. Therefore, cryptographic algorithms are frequently employed either in symmetric or asymmetric way [2]. The security of symmetric algorithms depends upon the network of the algorithm (e.g.…”
Section: Introductionmentioning
confidence: 99%